Sinergi Pemerintah Daerah dan Sektor Swasta dalam Pembangunan Pendidikan: Studi Kasus Program Astra Cerdas di Kecamatan Pasangkayu, Sulawesi Barat: Studi Kasus Program Astra Cerdas di Kecamatan Pasangkayu, Sulawesi Barat - Nurfadillah Nurfadillah; Sabania Amrina Rosada; St. Fahriah Rumambi; Norce Christianti Ta’ela; Yuliyana Abd Aziz; Nuraisyah Nuraisyah; Askar Mayusa; Muhammad Ahsan Samad (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study examines the synergy between local governments and the private sector in advancing regional education, focusing on the Astra Cerdas Program in Pasangkayu Regency. Despite the government's mandate to provide quality education, budget constraints often hinder optimal infrastructure and human resource development. This research employs a qualitative descriptive method with data collected through in-depth interviews, observation, and document analysis involving the Education Office, private sector representatives, and school principals. The findings indicate that collaborative governance through the Astra Cerdas program has positively impacted the educational ecosystem in Pasangkayu. The synergy is manifested in school infrastructure rehabilitation, teacher capacity building, and scholarship distributions. However, challenges such as bureaucratic synchronization and long-term sustainability persist. The implications of this study suggest that formalizing public-private partnerships through long-term memorandums of understanding can optimize educational outcomes in developing regions.